25x2 - 10xy + y2 = (5x - y)2
(y+2)(y+3)
4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]
4x2 - 4xy + y2 = (2x - y)2 so the length of the side of the square must be 2x-y.
The solution to the equation 2x plus 2 is 2(x + 1).
(2-r)e-rr
What do you want to convert it to? x2 + y2 = 2x If you want to solve for y: x2 + y2 = 2x ∴ y2 = 2x - x2 ∴ y = (2x - x2)1/2 If you want to solve for x: x2 + y2 = 2x ∴ x2 - 2x = -y2 ∴ x2 - 2x + 1 = 1 - y2 ∴ (x - 1)2 = 1 - y2 ∴ x - 1 = ±(1 - y2)1/2 ∴ x = 1 ± (1 - y2)1/2
If:xy = x2 + y2 + 2xyThen:x2 + xy + y2 = 0Do you want to solve it for x?x2 + xy + (y/2)2 = (y/2)2 - y2(x + y/2)2 = y2/4 - y2x + y/2 = ± √(-3y2/4)x = -y/2 ± y√(-3) / 2x = (-y ± yi√3) / 2
X2+y2=25 (x-8)2+y2 =41
There are several steps involved in how one can solve the derivative x plus y - 1 equals x2 plus y2. The final answer to this math problem is y'(x) = (1-2 x)/(2 y-1).
(y2+13y+22)/(y+2) = (y+11)
y2+7y=18 y2+7y-18=0 (y+9)(y-2)=0 y=-9 & y=2
3 raised to negative 2 would be -9 plus 6 to the negative 1 which is -6 so -9+-6=-15
Y²-5Y+4=0 Y1=-(-5/2) - Square root of ((-5/2)²-4) Y1= 2.5 - Square root of 2.25 Y1 = 1 Y2=-(-5/2) + Square root of ((-5/2)²-4) Y2= 2.5 + Square root of 2.25 Y2 = 4 Y can be either 1 or 4
y^2=-x^2-8x+6
25x2 - 10xy + y2 = (5x - y)2
a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z